2018
DOI: 10.2217/fon-2018-0303
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNAs as Biotargets in Cisplatin-Based Drug Resistance

Abstract: Since its discovery, cisplatin has become the key drug in chemotherapy for cancers. Nevertheless, chemoresistance in cancers has become an impediment in using cisplatin for cancer treatment. The resistance toward cisplatin is multifaceted as it involves multiple cellular pathways. Ever since the knowledge of long noncoding RNAs as modulators of various molecular pathways came to light, the interest in the biological function of lncRNAs as biomarkers has increased dramatically. Numerous studies have reported th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 84 publications
0
23
0
Order By: Relevance
“…[8][9][10] Moreover, dysregulated lncRNAs have been reported to be implicated with cisplatin resistance in various cancers. 11 LncRNA small nucleolar RNA host gene 15 (SNHG15), an intergenic lncRNA located on chromosome 7p13, belongs to a family of non-coding RNAs that hosting snoRNAs. 12 Previous studies suggest that SNHG15 could promote cancer cell proliferation and invasiveness and is able to play as a crucial determinant role in the chemoresistance.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Moreover, dysregulated lncRNAs have been reported to be implicated with cisplatin resistance in various cancers. 11 LncRNA small nucleolar RNA host gene 15 (SNHG15), an intergenic lncRNA located on chromosome 7p13, belongs to a family of non-coding RNAs that hosting snoRNAs. 12 Previous studies suggest that SNHG15 could promote cancer cell proliferation and invasiveness and is able to play as a crucial determinant role in the chemoresistance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, hypoxia, epithelial-mesenchymal transition, apoptosis inhibition and changes in molecular signalling pathways also contribute to drug resistance 10 . Studies have suggested that cisplatin resistance is related to regulation of the cell cycle, apoptosis and the Wnt pathway by long non-coding RNAs (lncRNAs) 11 . LncRNAs are small non-coding RNAs with more than 200 nucleotides and account for 80% of all non-coding RNAs.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 LncRNAs played important roles in the regulation of tumorigenesis and drug resistance in ovarian cancer. 27,28 Previous studies demonstrated that NEAT1 acted as an oncogenic lncRNA to promote the progression of ovarian cancer. 7,10 However, whether NEAT1 could regulate cisplatin resistance in ovarian cancer remains unclear.…”
Section: Discussionmentioning
confidence: 99%